Implementasi Model Pembelajaran Invesitigasi Kelompok Berbasis Pendekatan Saintifik Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran IPA Di Kelas IV SD Inpres 2 Tondo - Nurlinda Bilatu; Amram Rede; Indarini Dwi Pursitasari (Mitra Sains, 2016)
The study aimed to improve motivation and learning outcomes in science subject by implementing of group investigation learning model base on scientific approach was conducted on even semester in academic year 2014-2015. The research was classroom action research by 2 cycle. Each cycle consists of 2 meetings. The stage of each cycle are planning, action, observation, and reflection. The study result showed that learning motivation before action stage was 74% (good category), cycle I 84.03% (still in good category), cycle II 91% (excellent category). Another result was learning outcomes, it has average score 64% before action stage, in cycle I 71%, and cycle II 84%. The completeness level of classical score, before action stage was 43.3%, cycle I 87%, and cycle II 100%. Base on the result study could be concluded that implementation of group investigation learning model base on scientific approach in science subject can improve motivation and learning outcomes.